RESPON BEBERAPA VARIETAS JAGUNG (Zea mays L.) TERHADAP CEKAMAN ALUMINIUM - Yolanda Putri; Auzar Syarif; Nurwanita Ekasari Putri (Fakultas Pertanian, Universitas Janabadra, 2024)
Increasing corn production can be done by carrying out extensification in marginal areas, one of which is acidic soil. However, problems in acidic soil include low soil fertility and high Al content which can poison plants. One approach that can be taken is the use of tolerant corn varieties. This study aims to evaluate the growth and tolerance levels of several corn varieties to aluminum stress. The study was conducted from January to February 2024 at the Greenhouse of the Faculty of Agriculture, Tissue Culture Laboratory and Biology Laboratory of Andalas University. The study used a factorial Completely Randomized Design (CRD) with a concentration treatment of 0 ppm, 180 ppm AlCl3 and corn varieties, each consisting of three replications. Each replication consisted of 8 plants with 4 sample plants planted on seedbed media containing Hoagland nutrient solution composition. The results of the study from the six varieties evaluated showed that there were 3 varieties, namely P32, Bisi 18, and Lamuru, which were classified as somewhat tolerant to aluminum stress.